EFFECT OF ONLINE PAYMENT SECURITY ON THE BUYING BEHAVIOUR OF THE ONLINE SHOPPERS IN CHENNAI CITY - Vijayan, Parvathy; Duraisamy, Durairaj (The journal of contemporary issues in business and government, 2021)
Online shopping is flattering more accepted due to its ease and affordability. But that doesn‟t mean online shopping is with no flaw or drawbacks. Payment security is big question mark in the online shopping; consumers are facing such issues every day. To safeguard the interests of the online shopping consumers there are security systems and payment systems available to protect against deception and security related threats, but still there is a threat of security breaches for online stores. This present study examines the features of online payment security threats with reference to online shopping consumers‟ purchase intentions. This research further approached the online shopping customers in Chennai city as representatives and all those representatives were contacted by mail along with the questionnaires. The data was collected from 305 respondents and the Structural equation modeling (SEM) with Wrap-PLS is administered to examine the data. The findings of the research shows that a fit model to enlighten online shopping consumers‟ purchase intentions. The outcomes of the study expose a good mediating effect relationship of perceived usefulness on online payment security and purchase intentions of the customers. Further, the perceived ease of use also has an important indirect effect, all the way through digital payment security, on the purchase intentions of the online shopping customers. Moreover accepting the ease and adoption of the security sides of the payment affect the purchase intentions of the online shopping consumers. The outcomes of the research also give more awareness over various security aspects in electronic transactions.